Representações de esporte e lazer na ditadura civil-militar: uma análise a partir do jornal Podium (1972-1974) - Anderton Taynan Rocha Fonseca (2023)
In the 1970s, a period in which Brazil was undergoing a dictatorship, the Federal Government, through the Department of Physical Education and Sports of the Ministry of Education and Culture, carried out the National Campaign for Sports Enlightenment. This campaign distributed several advertisements on a national scale. Among these materials was the newspaper Podium. The means of communication sought to prescribe representations of sport and leisure that would be useful for the creation of a strong nation and consistent with the regime's designs, thus, the Podium newspaper was a privileged object to observe how the government used advertising resources to spread its interests to the Brazilian people. The objective of this research was to analyze which representations of sport and leisure circulated in this journal. In the case of the methodology for the development of this Dissertation, a literature review was carried out, dialoguing with studies that addressed themes related to the History of Sport, Leisure and Physical Education in the period of the civil-military dictatorship in Brazil and the use of printed matter as source and object, as well as based on Discourse Analysis. The investigations carried out made it possible to understand how the National Campaign for Sports Enlightenment was articulated through the Podium newspaper to propagate a popular atmosphere of incentive to sports practices that it called “sports mentality”.